Current and future burden of breast cancer in Asia: A GLOBOCAN data analysis for 2022 and 2050 - Mengxia Fu; Zhiming Peng; Min Wu; Dapeng Lv; Yanping Li; Shuzhen Lyu (Breast)
Background: Breast cancer remains a significant health concern in Asia. This study seeks to analyze the burden of breast cancer in Asia based on the most recent GLOBOCAN 2022 estimates. Methods: Data were obtained from GLOBOCAN 2022. Age-standardized rates for incidence and mortality per 100,000 person-years were calculated using direct age standardization with the Segi-Doll World standard population. Pearson's correlation coefficient was utilized to evaluate the relationship between human development index and incidence or mortality rate. The future number of breast cancer cases and deaths by 2050 was estimated based on global demographic projections. Results: In 2022, breast cancer accounted for 2296.8 thousand new cases and 666.1 thousand deaths worldwide. In Asia, an estimated 985.4 thousand new cases and 315.1 thousand deaths were reported, corresponding to age-standardized incidence and mortality rates of 34.3 and 10.5 per 100,000, respectively. Both incidence and mortality rates were notably higher among older individuals, especially in countries with high human development index. A positive correlation between human development index and incidence rates was observed, while mortality rates were highest in countries with low human development index. China and India are the leading contributors to both new cases and deaths, with projections indicating that by 2050, around 1.4 million new breast cancer cases and 0.5 million deaths are expected to occur in Asia. Conclusion: Breast cancer is the most common cancer among women in Asia. Global collaboration is essential to reduce its growing burden, especially in low-HDI countries facing rising incidence and high mortality rates.